The Reconciliation Project: Separation and Integration in Business Ethics Research - Alzola, Miguel (2011)
This article is about the relationship between business and ethics in academic research. The purpose of this investigation is to examine the status of the separation and the integration theses. In the course of this article, I defend the claim that neither separation nor integration is entirely accurate; indeed they are both potentially confusing to our audience. A strategy of reconciliation of normative and descriptive approaches is proposed. The reconciliation project does not entail synthesizing or dividing prescriptive and empirical approaches, but rather respecting the identity of both inquiries, while recognizing the limitations they place on each other. The research agenda of the reconciliation project is discussed.
Keywords: integration thesis; Separation Thesis; business ethics research